Decarbonizing Development : Three Steps to a Zero-Carbon Future - Fay, Marianne (Washington, DC: World Bank, 2015)
The science is unequivocal: stabilizing climate change implies bringing net carbon emissions to zero. And this must be done by 2100 if we are to keep climate change anywhere near the 2 C. degree warming that world leaders have set as the maximum acceptable limit. Decarbonizing Development looks at what it would take to decarbonize the world economy by 2100 in a way that is compatible with countries’ broader development goals. It argues that the following are needed: Act early with an eye on the end-goal; Go beyond prices with a policy package that triggers changes in investment patterns, technologies and behaviors; Mind the political economy and smooth the transition for those who stand to be most affected.